Appraisal of Socio- Economic and Political Thoughts of Rammanohar Lohia in Contemporary India - Kumar, Prof. Kamal (The journal of contemporary issues in business and government, 2021)
The contribution of socialist leader Dr Rammanohar Lohia during the freedom struggle and his socio-economic and political views has been praiseworthy in the contemporary India. Lohia was a visionary leader. While Marx's views were mostly based on economic disparity, Lohia on the contrary made the basis of his ideological crusade as socio- economic and cultural disparity along with search of political power for the common man. He gave the concept of "Saptkranti" and raised his voice against the different aspects of exploitations of poor masses. Lohia's ideological thoughts on different political, social and economic issues such as question of world citizen, means of Nation's economic development, social evils like caste system and the poor's participation in the political power structure, and most important his views on socialism made him world famous socialist leader and thinker of contemporary India. His thoughts on international affairs and particularly on the question of Indian Foreign Policy gave him the political recognition among the contemporary world leaders. Against this backdrop, present paper attempts to review the socio- economic and political views of Dr. Rammanohar Lohia.